Dynamics of Cell Fate Decisions during Chemically Induced Multi‐Lineage Trans‐Differentiation at Single‐Cell Level - Weigao E; Lijiang Fei; Jingjing Wang; Xinru Wang; Renying Wang; Xueyi Wang; Peijing Zhang; Jianhui Chen; Junqing Wu; Mengmeng Jiang; Daosheng Huang; Danmei Jia; et al. (Advanced Science)
Abstract Cell trans‐differentiation offers a powerful means to manipulate cell identities. By exposing cells to a combination of small molecules (SMs), cell trans‐differentiation can be induced in a simple and cost‐effective manner. However, a comprehensive atlas detailing chemical‐induced cell trans‐differentiation across multiple cell fates has yet to be established. In this study, the underlying mechanisms of trans‐differentiation is investigated and constructed an in‐depth single‐cell atlas of this process. The time‐course trajectory is demonstrated for trans‐differentiation of mouse embryonic fibroblasts (MEFs) into multiple cell lineages including epithelial, neural, extraembryonic endoderm like (XEN‐like) cells, and endothelial cells, when induced by SMs cocktail 6TCF (E616452, tranylcypromine, CHIR99021, and forskolin). These trans‐differentiated cells closely resemble various somatic cell types in the fetus. It is found that trans‐differentiation is marked by dynamic shifts in entropy and the cell cycle during cell fate transitions. A common intermediate feature is revealed characterized by high ribosomal gene expression. This study combines high‐resolution landscape with comparative analyses of trans‐differentiation dynamics, providing new insights into the complex mechanisms driving cell fate determination in vitro. Future study shall explore the applicability of the model in human cell trans‐differentiation.